Հայոց պետականության վերականգնման առաջին քաղաքական փորձը և դրա ձախողման դրդապատճառները - Հայկ Մարգարյան (ՀՀ ԳԱԱ հրատ.)
После падения армянского киликийского царства (1375 г.) стремление к восстановлению государственности господствовало в умах представителей духовных и светских сословий. Первую попытку восстановления армянской государственности предпринял католикос Ахтамара Закариа Г. Он свои политические программы призвал к жизни при помощи владыки каракоюнов Джаханшаха (1437-1467г.).This article is about the endeavor to restore the statehood of the Cilician Armenian kingdom after its fall in1375. This endeavor dominated the outlook of the representatives of the Armenian religious and secular classes. Catholicos Zaqaria “C” of Aghtamar was the first who attempted to restore the Armenian statehood with the help of Jhanshah who was the shah of Kara - Koyunlun (1437-1467).
Keywords: Medieval History; Political Science